Semi-interpenetrating high-temperature proton exchange membrane based on imidazolyl polyion liquid and preparation method of semi-interpenetrating high-temperature proton exchange membrane

By introducing silicon oxygen crosslinking network and 1-alkylimidazole polyvinylbenzyl chloride polyionic liquid into the proton exchange membrane, a semi-interpenetrating structure is formed, which solves the problem of insufficient mechanical properties and phosphoric acid retention rate of the existing proton exchange membrane under high temperature conditions, and achieves higher mechanical properties and phosphoric acid retention rate, extending the service life of the fuel cell.

CN119812413APending Publication Date: 2025-04-11CHANGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510163237.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing proton exchange membranes have insufficient mechanical properties and phosphoric acid retention under high temperature conditions, which affects the service life and performance of fuel cells.

Method used

By introducing silicon oxygen cross-linking network and 1-alkylimidazole polyvinylbenzyl chloride polyionic liquid, a semi-interpenetrating structure is formed, which improves the mechanical properties and phosphoric acid absorption of the proton exchange membrane.

Benefits of technology

It significantly improves the mechanical properties, chemical stability and phosphoric acid retention of the proton exchange membrane, extends the service life of the fuel cell and improves its performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812413A_ABST
    Figure CN119812413A_ABST
Patent Text Reader

Abstract

The invention relates to a high-temperature proton exchange membrane, in particular to a semi-interpenetrating high-temperature proton exchange membrane based on imidazolyl polyion liquid and a preparation method of the semi-interpenetrating high-temperature proton exchange membrane. The preparation method comprises the following steps: dissolving polybenzimidazole, a silane coupling agent and the imidazolyl polyionic liquid in dimethyl sulfoxide to obtain a mixture, spreading and drying the mixture to prepare a membrane, and performing acid catalysis to form a silicon-oxygen cross-linked structure, thereby obtaining the semi-interpenetrating high-temperature proton exchange membrane based on the imidazolyl polyionic liquid. A silicon-oxygen cross-linked network structure is introduced into the proton exchange membrane, so that the oxidation resistance and tensile strength of the membrane can be improved, and the swelling rate of the acid-doped membrane can be reduced; the phosphoric acid adsorption rate can be improved by introducing the imidazolyl polyion liquid, so that the proton conductivity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-temperature proton exchange membrane, in particular to a semi-interpenetrating high-temperature proton exchange membrane based on imidazole-based polyionic liquid and a preparation method thereof. Background Art

[0002] The proton exchange membrane (PEM) plays the role of transferring protons from the anode to the cathode and isolating the gas, and is the core component of the proton exchange membrane fuel cell. Polybenzimidazole has good mechanical properties and excellent thermal stability, and is very suitable as a proton exchange membrane, but its own proton conductivity is very poor, and it relies on phosphoric acid to improve its proton conductivity. The doping of phosphoric acid will reduce the mechanical properties of the proton exchange membrane, affect the service life of the proton exchange membrane and the fuel cell, and the loss of phosphoric acid will also reduce the proton conductivity of the membrane. Therefore, the development of a PBI proton exchange membrane with high phosphoric acid absorption rate, high mechanical properties and high phosphoric acid retention rate has a significant driving effect on fuel cells. Summary of the invention

[0003] In order to prepare a high-temperature proton exchange membrane with high phosphate absorption rate, high mechanical properties and high phosphate retention rate, the present invention introduces a silane coupling agent into polybenzimidazole to form a silicon-oxygen cross-linked network, and adds 1-alkylimidazole polyvinylbenzyl chloride polyionic liquid to form a semi-interpenetrating structure, thereby improving the mechanical properties and chemical stability of the proton exchange membrane.

[0004] The preparation method of the high-temperature proton exchange membrane is as follows: polybenzimidazole, a silane coupling agent and an imidazole-based polyionic liquid are dissolved in dimethyl sulfoxide (DMSO) to obtain a mixture, which is spread and dried at 60° C. to form a membrane, and then the membrane is placed in 85% phosphoric acid and heated at 80° C. for 24 hours, washed with deionized water until the washing liquid is neutral, and dried at 60° C. to obtain a semi-interpenetrating high-temperature proton exchange membrane based on imidazole-based polyionic liquid.

[0005] Polybenzimidazole is a polybenzimidazole containing ether bonds and phenolic hydroxyl groups. The preparation method is as follows: in a nitrogen atmosphere, at 100°C, the monomer is dissolved in polyphosphoric acid, the temperature is raised to 120°C for polymerization for 2 hours, and then the temperature is raised to 200°C for polymerization until the solution climbs, the solution is poured into deionized water, and the washing liquid is washed with boiling water until it is neutral, and the polybenzimidazole is obtained by filtering and drying. The monomer is composed of 3,3'-diaminobiphenyl (DAB), 4,4'-diphenyl ether dicarboxylic acid (OBBA) and 5-hydroxyisophthalic acid (OHIPA).

[0006] The molar ratio of 3,3'-diaminobiphenyl to the total molar ratio of OBBA and OHIPA is 1:1, and the mass of the monomer is 6%-12% of the mass of the polyphosphoric acid.

[0007] Silane coupling agents include, but are not limited to, 3-chloropropyltrimethoxysilane (CPTOM) or 3-isocyanatopropyltrimethoxysilane (IPTS).

[0008] The added amount of polybenzimidazole is 2% of the mass of dimethyl sulfoxide (DMSO), the mass of the silane coupling agent is 5% of the mass of the polybenzimidazole, and the mass of the imidazole-based polyionic liquid is (0,30%) of the mass of the polybenzimidazole.

[0009] The imidazole-based polyionic liquid is: 1-alkylimidazole polyvinylbenzyl chloride, and its synthesis method is: vinylbenzyl chloride and a corresponding mass of AIBN are dissolved in an organic solvent, and the reaction is condensed and refluxed at 65°C for 24 hours under a nitrogen atmosphere, and the solution obtained by the reaction is dripped into anhydrous ether, washed several times, and rotary evaporated to obtain polyvinylbenzyl chloride, and polyvinylbenzyl chloride and a corresponding molar mass of N-alkylimidazole are dissolved in an organic solvent, and the reaction is condensed and refluxed at 50°C for 24 hours, and the reaction solution is dripped into anhydrous ether, washed several times, and rotary evaporated to obtain a water-insoluble imidazole polyionic liquid.

[0010] The mass of azobisisobutyronitrile (AIBN) is 1% of the mass of vinylbenzyl chloride, the molar mass of N-alkylimidazole is (0.50%] of the molar mass of polyvinylbenzyl chloride, and N-alkylimidazole is N-methylimidazole, N-ethylimidazole, 1,2-dimethylimidazole, etc. The organic solvent includes but is not limited to dimethyl sulfoxide (DMSO), N,N-dimethylacetamide (DMAc), and N,N-dimethylformamide (DMF).

[0011] Compared with the prior art, the present invention has the following advantages:

[0012] (1) Introducing a silicon-oxygen cross-linked network structure into the proton exchange membrane can improve the membrane's antioxidant properties and tensile strength, and can also reduce the swelling rate of the acid-doped membrane;

[0013] (2) The introduction of imidazolyl polyionic liquid into the proton exchange membrane can increase the phosphate adsorption rate and thus improve the proton conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is the H NMR spectrum of polybenzimidazole containing ether bonds and phenolic hydroxyl groups and 1-methylimidazole polyvinylbenzyl chloride. DETAILED DESCRIPTION

[0015] The present invention will be further described below with reference to the embodiments.

[0016] Example 1

[0017] In a nitrogen atmosphere, 2.1432 g of DAB, 1.6482 g of OBBA and 0.7062 g of OHIPA were dissolved in 56.2 g of polyphosphoric acid at 100 °C. After the drugs were completely dissolved, the temperature was raised to 120 °C for prepolymerization for 2 hours, and then the temperature was raised to 200 °C for polymerization until the liquid climbed. The liquid was poured into deionized water, washed with boiling water until the washing liquid was neutral, and filtered and dried to obtain 3.9 g of polybenzimidazole containing ether bonds and phenolic hydroxyl groups.

[0018] 2g of vinylbenzyl chloride and 0.02g of azobisisobutyronitrile (AIBN) were dissolved in 3ml of dimethyl sulfoxide (DMSO), reacted at 65°C for 24h under nitrogen atmosphere, the reaction solution was dropped into anhydrous ether and washed 3 times, and 1.8g of polyvinylbenzyl chloride was obtained by rotary evaporation. 1.53g of polyvinylbenzyl chloride and 0.041g of N-methylimidazole were dissolved in 15ml of dimethyl sulfoxide (DMSO), reacted at 50°C for 24h, washed 3 times with ether, and 2.13g of 50% quaternized 1-methylimidazole polyvinylbenzyl chloride was obtained by rotary evaporation.

[0019] Dissolve 0.2g of polybenzimidazole containing ether bonds and phenolic hydroxyl groups in 10ml of dimethyl sulfoxide to form a polybenzimidazole solution. Add 0.01g of 3-isocyanate propyl trimethoxysilane to the polybenzimidazole solution, react at 50°C for 24h under a nitrogen atmosphere to obtain a grafted polybenzimidazole containing ether bonds and phenolic hydroxyl groups, dissolve 0.01g of 50% quaternized 1-methylimidazole polyvinyl benzyl chloride salt therein, drop the mixture onto a glass plate, place it in an oven at 60°C for 24h and dry it flat to form a film. Immerse the membrane in 85% phosphoric acid, heat it at 80°C for 24h to form a silicon-oxygen cross-linked structure, wash until the washing liquid is neutral, and dry it at 60°C to obtain a semi-interpenetrating high-temperature proton exchange membrane.

[0020] The proton conductivity of the membrane is 81.59 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 275.89%, and the tensile strength was 63.54MPa. After being placed at 100°C for 120h, the phosphoric acid retention rate was 85.6%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 120h, washed and dried, and its remaining weight was measured to be 86.9% of the original mass, proving that the membrane has good chemical stability.

[0021] Example 2

[0022] The steps of this embodiment are basically the same as those of embodiment 1, except that the amount of 50% quaternized 1-methylimidazole polyvinylbenzyl chloride used is 0.02 g.

[0023] The proton conductivity of the membrane is 86.72 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 286.73%, and the tensile strength was 65.68MPa. After being placed at 100°C for 120h, the phosphoric acid retention rate was 87.95%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 120 hours, and after washing and drying, its remaining weight was measured to be 88.45% of the original mass, proving that the membrane has good chemical stability.

[0024] Example 3

[0025] The steps of this embodiment are basically the same as those of Example 1, and the difference from Example 1 is that when preparing quaternized 1-methylimidazole polyvinyl benzyl chloride, the amount of N-methylimidazole added is 0.0246 g, and the obtained imidazole-based polyionic liquid is 30% quaternized 1-methylimidazole polyvinyl benzyl chloride.

[0026] The proton conductivity of the membrane is 78.41 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 273.52%, and the tensile strength was 64.59MPa. After being placed at 100°C for 120h, the phosphoric acid retention rate was 84.3%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 120 hours, and after washing and drying, its remaining weight was measured to be 87.1% of the original mass, proving that the membrane has good chemical stability.

[0027] Example 4

[0028] The steps of this embodiment are basically the same as those of embodiment 1, and the difference from embodiment 1 is that the silane coupling agent is 3-chloropropyltrimethoxysilane.

[0029] The proton conductivity of the membrane is 76.14 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 279.75%, and the tensile strength was 62.45MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 86.1%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O2 ), placed at 80°C for 120 hours, and after washing and drying, its remaining weight was measured to be 86.4% of the original mass, proving that the membrane has good chemical stability.

[0030] Example 5

[0031] The steps of this embodiment are basically the same as those of Example 1, except that the amount of polyphosphoric acid added is 45.0 g.

[0032] The proton conductivity of the membrane is 80.96 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 274.99%, and the tensile strength was 62.81MPa. After being placed at 100°C for 120h, the phosphoric acid retention rate was 85.7%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 120h, washed and dried, and its remaining weight was measured to be 86.7% of the original mass, proving that the membrane has good chemical stability.

[0033] Example 6

[0034] The steps of this embodiment are basically the same as those of embodiment 1, except that the amount of 50% quaternized 1-methylimidazole polyvinylbenzyl chloride used is 0.03 g.

[0035] The proton conductivity of the membrane is 90.13 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 396.55%, and the tensile strength was 64.76MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 88.29%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 120 hours, and after washing and drying, its remaining weight was measured to be 87.85% of the original mass, proving that the membrane has good chemical stability.

[0036] Example 7

[0037] The steps of this embodiment are basically the same as those of Example 1, and the difference from Example 1 is that when preparing quaternized 1-methylimidazole polyvinyl benzyl chloride, the amount of N-methylimidazole added is 0.0082 g, and the obtained imidazole-based polyionic liquid is 10% quaternized 1-methylimidazole polyvinyl benzyl chloride.

[0038] The proton conductivity of the membrane is 75.69 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 260.19%, and the tensile strength was 65.29MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 83.9%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 120 hours, and after washing and drying, its remaining weight was measured to be 87.2% of the original mass, proving that the membrane has good chemical stability.

[0039] Example 8

[0040] The steps of this embodiment are basically the same as those of embodiment 1, except that: N-methylimidazole is not added, but 0.048 g of 1,2-dimethylimidazole is added.

[0041] The proton conductivity of the membrane is 80.99 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 274.46%, and the tensile strength was 63.46MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 85.3%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 120h, washed and dried, and its remaining weight was measured to be 86.7% of the original mass, proving that the membrane has good chemical stability.

[0042] Comparative Example 1

[0043] In a nitrogen atmosphere, 2.1432 g of DAB, 1.6482 g of OBBA and 0.7062 g of OHIPA were dissolved in 56.2 g of polyphosphoric acid at 100 °C. After the drugs were completely dissolved, the temperature was raised to 120 °C for prepolymerization for 2 hours, and then the temperature was raised to 200 °C for polymerization until the liquid climbed. The liquid was poured into deionized water, washed with boiling water until the washing liquid was neutral, and filtered and dried to obtain 3.9 g of polybenzimidazole containing ether bonds and phenolic hydroxyl groups.

[0044] Dissolve 0.2g of polybenzimidazole containing ether bonds and phenolic hydroxyl groups in 10ml of dimethyl sulfoxide to form a polybenzimidazole solution. Add 0.01g of 3-isocyanate propyltrimethoxysilane to the polybenzimidazole solution, react at 50°C for 24h under a nitrogen atmosphere, drop the mixed solution onto a glass plate, place it in an oven at 60°C for 24h and dry it flat to form a film. Immerse the membrane in 85% phosphoric acid, heat it at 80°C for 24h to form a silicon-oxygen cross-linked structure, wash until the washing liquid is neutral, and dry it at 60°C to obtain a semi-interpenetrating high-temperature proton exchange membrane.

[0045] The proton conductivity of the membrane is 61.15 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 220.11%, and the tensile strength was 64.89MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 79.6%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 120 hours, and after washing and drying, its remaining weight was measured to be 82.6% of the original mass, proving that the membrane has good chemical stability.

[0046] Comparative Example 2

[0047] Under nitrogen atmosphere, 2.1432g DAB, 1.6482g OBBA and 0.7062g OHIPA were dissolved in 56.2g polyphosphoric acid at 100°C. After the drugs were completely dissolved, the temperature was raised to 120°C for prepolymerization for 2h, and then raised to 200°C for polymerization until the liquid climbed. The liquid was poured into deionized water, washed with boiling water several times until the washing liquid was neutral, and filtered and dried to obtain 3.9g of polybenzimidazole containing ether bonds and phenolic hydroxyl groups.

[0048] 0.2 g of polybenzimidazole containing ether bonds and phenolic hydroxyl groups was dissolved in 10 ml of dimethyl sulfoxide to form a polybenzimidazole solution, which was spread and dried at 60° C. for 24 hours to form a film.

[0049] The proton conductivity of the membrane is 69.8 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 268.5%, and the tensile strength was 42.85MPa. After being placed at 100°C for 120h, the phosphoric acid retention rate was 63.8%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 120 hours, and after washing and drying, its remaining weight was measured to be 70.6% of the original mass, proving that the membrane has good chemical stability.

[0050] Comparative Example 3

[0051] Under nitrogen atmosphere, 2.1432g DAB and 2.5823g OBBA were dissolved in 56.2g polyphosphoric acid at 100°C. After the drugs were completely dissolved, the temperature was raised to 120°C for prepolymerization for 2h, and then raised to 200°C for polymerization until the liquid climbed. The liquid was poured into deionized water, washed with boiling water several times until the washing liquid was neutral, and filtered and dried to obtain 3.9g of polybenzimidazole containing ether bonds and phenolic hydroxyl groups.

[0052] 0.2 g of polybenzimidazole containing ether bonds was dissolved in 10 ml of dimethyl sulfoxide to form a polybenzimidazole solution, which was spread and dried at 60°C for 24 hours to form a film.

[0053] The proton conductivity of the membrane is 54.8 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 249.5%, and the tensile strength was 40.58MPa. After being placed at 100°C for 120h, the phosphoric acid retention rate was 60.1%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 120 hours, and after washing and drying, its remaining weight was measured to be 70.0% of the original mass ratio, proving that the membrane has good chemical stability.

Claims

1. A method for preparing a semi-interpenetrating high-temperature proton exchange membrane based on imidazole-based polyionic liquid, characterized in that: The preparation method comprises the following steps: dissolving polybenzimidazole, a silane coupling agent and an imidazole-based polyionic liquid in dimethyl sulfoxide, spreading the obtained mixture flat and drying it at 60°C to form a membrane, and then placing the membrane in 85% phosphoric acid and heating it at 80°C for 24 hours, washing it, and drying it at 60°C to obtain a semi-interpenetrating high-temperature proton exchange membrane based on the imidazole-based polyionic liquid.

2. The method for preparing a semi-interpenetrating high temperature proton exchange membrane based on imidazole-based polyionic liquid according to claim 1, characterized in that: The preparation method of polybenzimidazole is as follows: in a nitrogen atmosphere, at 100°C, the monomer is dissolved in polyphosphoric acid, the temperature is raised to 120°C for polymerization for 2 hours, and then the temperature is raised to 200°C for polymerization until the solution reaches a certain temperature, the solution is poured into deionized water, and the solution is washed with boiling water until the washing liquid is neutral, and the polybenzimidazole is obtained by filtering and drying. The monomer is composed of 3,3'-diaminobiphenyl DAB, 4,4'-diphenylether dicarboxylic acid OBBA and 5-hydroxyisophthalic acid OHIPA.

3. The method for preparing a semi-interpenetrating high temperature proton exchange membrane based on imidazole-based polyionic liquid according to claim 2, characterized in that: The total molar ratio of 3,3'-diaminobiphenyl to OBBA and OHIPA is 1:1, and the mass of the monomer is 6%-12% of the mass of the polyphosphoric acid.

4. The method for preparing a semi-interpenetrating high temperature proton exchange membrane based on imidazole-based polyionic liquid according to claim 1, characterized in that: The silane coupling agent is: 3-chloropropyltrimethoxysilane CPTOM or 3-isocyanatepropyltrimethoxysilane IPTS; the amount of the silane coupling agent is 5% of the mass of the polybenzimidazole.

5. The method for preparing a semi-interpenetrating high temperature proton exchange membrane based on imidazole-based polyionic liquid according to claim 1, characterized in that: The amount of polybenzimidazole added is 2% of the mass of dimethyl sulfoxide; the mass ratio of imidazole-based polyionic liquid to polybenzimidazole is greater than 0 and less than or equal to 30%.

6. The method for preparing a semi-interpenetrating high temperature proton exchange membrane based on imidazole-based polyionic liquid according to claim 1, characterized in that: The imidazole-based polyionic liquid is: 1-methylimidazole polyvinylbenzyl chloride, and its synthesis method is: vinylbenzyl chloride and azobisisobutyronitrile are dissolved in an organic solvent, and the reaction is condensed and refluxed at 65°C for 24 hours under a nitrogen atmosphere, and the solution obtained by the reaction is dripped into anhydrous ether, washed, and rotary evaporated to obtain polyvinylbenzyl chloride; then polyvinylbenzyl chloride and N-alkylimidazole are dissolved in an organic solvent, and the reaction is condensed and refluxed at 50°C for 24 hours, and the reaction solution is dripped into anhydrous ether, washed, and rotary evaporated to obtain the imidazole-based polyionic liquid.

7. The method for preparing a semi-interpenetrating high temperature proton exchange membrane based on imidazole-based polyionic liquid according to claim 6, characterized in that: The dosage of azobisisobutyronitrile is 1% of the mass of vinylbenzyl chloride, the molar ratio of N-alkylimidazole to chloromethylstyrene is greater than 0 and less than or equal to 50%, and the N-alkylimidazole is: N-methylimidazole, N-ethylimidazole, 1,2-dimethylimidazole.

8. The method for preparing a semi-interpenetrating high temperature proton exchange membrane based on imidazole-based polyionic liquid according to claim 6, characterized in that: The organic solvents are: dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide.

9. A semi-interpenetrating high temperature proton exchange membrane based on imidazolyl polyionic liquid prepared according to the method according to any one of claims 1 to 8.

10. An application of a semi-interpenetrating high temperature proton exchange membrane based on imidazole-based polyionic liquid prepared by the method according to any one of claims 1 to 8, characterized in that: The proton exchange membrane is used for a high-temperature proton exchange membrane fuel cell.

Citation Information

Cited By

  • A proton exchange membrane and a method for preparing the same

    CN122822824A